Quality Assurance in Private Higher Education in China - Osman Ozturgut (Arizona State University, 2011)
The economic modernization drive of the 21st century has not only fostered the growth of a market economy but has also created the need for a structural change in education (Zha, 2006). Mok (2009) explains that when the Chinese government realized that the state alone could not keep up with the increasing demand for higher education, it allowed non-governmental institutions to get involved. However, with the fast expansion of the private higher education system, maintaining educational quality and integrity has not been a priority. Administrators have been rather incompetent in hiring qualified faculty and staff. They have minimum or no experience in curriculum and program development. Laboratory facilities and technological services are insufficient and living and learning conditions for students, staff, and faculty are far from satisfactory. Chinaâs private higher education needs a major overhaul even from the start.